2014
DOI: 10.1152/jn.00439.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of visual and haptic feedback on grasping movements

Abstract: Bozzacchi C, Volcic R, Domini F. Effect of visual and haptic feedback on grasping movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 49 publications
6
21
0
Order By: Relevance
“…Based on the empirical evidence that binocular cues do not yield an accurate metric space representation (Bingham et al 2001;Volcic et al 2013;Johnston et al 1991;Brenner et al 1997;Brenner and van Damme 1999;Hibbard and Bradshaw 2003), we expect to find a modulation of the MGA as function of distance in the virtual condition, where only binocular cues are available, resembling the effects previously described for perceptual and grasping tasks (Volcic et al 2013;Bozzacchi et al 2014). Specifically, we predict a reduction of the MGA of ϳ3 mm per 100 mm separating the closest from the furthest object distance (slope: ϳ0.03).…”
supporting
confidence: 68%
See 4 more Smart Citations
“…Based on the empirical evidence that binocular cues do not yield an accurate metric space representation (Bingham et al 2001;Volcic et al 2013;Johnston et al 1991;Brenner et al 1997;Brenner and van Damme 1999;Hibbard and Bradshaw 2003), we expect to find a modulation of the MGA as function of distance in the virtual condition, where only binocular cues are available, resembling the effects previously described for perceptual and grasping tasks (Volcic et al 2013;Bozzacchi et al 2014). Specifically, we predict a reduction of the MGA of ϳ3 mm per 100 mm separating the closest from the furthest object distance (slope: ϳ0.03).…”
supporting
confidence: 68%
“…Furthermore, errors similar to those in perceptual estimates were also found for grasping movements towards target objects only defined by binocular information (Bingham et al 2007;Hibbard and Bradshaw 2003;Bozzacchi et al 2014). In particular, by using virtual reality setups, we observed that even at the presence of both visual and haptic feedback, the grip aperture (GA) decreases with the increase of object egocentric distance, a clear index of depth constancy failure (Bozzacchi et al 2014). Remarkably, the effects reported in our previous study are strongly consistent with findings from perceptual paradigms.…”
mentioning
confidence: 57%
See 3 more Smart Citations